PERANAN KELOMPOK TANI DALAM PENGELOLAAN MADU LEBAH HUTAN (APIS DORSATA FABRICIUS) OLEH MASYARAKAT DI DESA NANGA LEBOYAN KECAMATAN SELIMBAU KAWASAN DANAU SENTARUM KABUPATEN KAPUAS HULU - Aini, Laila Quratul; M, Iskandar A; Hardiansyah, Gusti (JURNAL HUTAN LESTARI, 2019)
Sustainable management of forest honey requires an organization especially to guarantee forest honey quality standards in terms of naturalness which can be in the form of farmer groups. This study aims to reveal the role of farmer groups in the management of forest honey bees. This research is expected to provide information on how the role of farmer groups in the management of forest honey bees by the community in Nanga Leboyan Village, Selimbau District, Danau Sentarum Regency, Kapuas Hulu Regency. This research was conducted by conducting direct interviews with forest honey bee farmer groups. Information about the role of farmer groups in forest honey bee management was obtained during interviews and direct observations in the form of honey management processes, the role of farmer groups in institutions, production, capital, and the relationship between the role of farmer groups and the productivity of honey farming presented in tables, figures and The photo is then analyzed descriptively qualitatively. The results of interviews with 70 members of the honey farmer group showed that the process of forest honey management in Nanga Leboyan Village was carried out according to stages, starting from the initial installation of the bend to post-harvest. Farmer groups play an important role in their institutions, production and capital. The relationship between the role of farmer groups with the productivity of honey farming in Nanga Leboyan Village can be positively related to increasing honey production.Keywords: farmer groups, forest honey bee management, Role.